1998
DOI: 10.1007/s007870050039
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcome of children treated for depression

Abstract: Fifty-four children and adolescents (age 8-17) were assessed two years after a clinical intervention trial of cognitive-behavioural vs. non-focused treatment for depression. Eleven (20.4%) subjects fulfilled criteria for depression, while 21 (38.9%) reported significant depressive symptoms during the previous year. Seventeen young people (31.5%) had a psychiatric disorder (including depression). Overall, the sample maintained the improvement since the termination of treatment, without detecting specific treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 18 publications
2
28
0
4
Order By: Relevance
“…Of these children, 33.3 % showed a clinically significant reduction in level of psychopathology, plus an improvement of QoL. However, in accordance with previous studies [6,11,29] …”
Section: ■ Improvement Of Qolsupporting
confidence: 88%
See 2 more Smart Citations
“…Of these children, 33.3 % showed a clinically significant reduction in level of psychopathology, plus an improvement of QoL. However, in accordance with previous studies [6,11,29] …”
Section: ■ Improvement Of Qolsupporting
confidence: 88%
“…Furthermore, treatment outcome studies in children and adolescents revealed that interventions may result in complete reduction of psychiatric symptoms in a number of patients, but, often, recovery is partial, or even absent [2,18,24,29]. Hence, it might be worthwhile also focussing on minimizing the impact of symptoms on the child's functioning and on improving the child's quality of everyday life [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51,107,133 There were no studies on psychosis. Most (31/71) of the studies concerned interventions that could be classified as treatments (see Chapter 1, Intervention levels), [48][49][50][51][52]55,65,66,70,71,74,77,78,81,[83][84][85][86]91,[94][95][96][97][98][101][102][103][104]106,111,112,[121][122][123][124][125][126][127][129][130][131]133,135,139 with the remainder focusing equally on indicated (n = 11), 53,58,59,…”
Section: Description Of the Included Effectiveness Studiesmentioning
confidence: 99%
“…All of these investigations are notable for their use of help-seeking samples, whether depressed adolescent outpatients or youths involved with the social service system. Vostanis and colleagues [35,43,44] compared brief CBT to supportive therapy in a sample of depressed teen outpatients and found no difference between the treatment groups in depression response (86% versus 75%). In this investigation, treatment not only was low dose (mean of six sessions) but also was offered over an extended time frame (1-5 months).…”
Section: Brief Cognitive Behavioral Therapymentioning
confidence: 99%